ANALISA BREAKEVEN POINT (BEP) DAN TINGKAT KEUNTUNGAN STUDI KASUS: USAHA GENTENG RAHAYU DI KAB. TABANAN, BALI - I Wayan Adi Merta; Sunarsih Sunarsih; Bagus Qomaruzzaman (STIE Mandala Jember, 2013)
Businnes of production Rahayu is a tile-making business is kind of small press located in the Tabanan Regency, Bali. In conducting the business of production Rahayu tiles using simple tools and production quantities depending on the season (dry season and rainy) so that profit is not the same in each season. To determine the performance of the tiles Enterprises Rahayu, the study will analyze the level of Break Even Point (the breakeven point), Shut Down point (point-of-business), and the level of benefits to the individual - each season. This research method to analyze the breakeven point, point-of-business, and business profitability Tile Rahayu mathematically using production data from 2010 to 2012. The results obtained are the BEP analysis, business break even lower during the rainy season than during the dry season. This is because the selling price higher during the rainy season than during the dry season. Judging from the SDP analysis, point-of-business is much lower than the breakeven point in any season. This is due to fixed costs in cash on SDP analysis is much smaller than the total fixed cost of the BEP analysis. If the views of each season, the SDP during the rainy season is less than during the dry season due to monsoon selling price is higher than during the dry season. Judging from the level of profits, the two seasons (wet and dry) Tile Enterprises Rahayu produce nearly the same amount of profit, but profit is higher during the rainy season than during the dry season. This is due to the selling price higher during the rainy season so that revenue also grew, as well as variable costs during the rainy season due to lower production numbers lower than the dry season, thereby reducing production costs.